Structural colors in the realm of nature - Kinoshita, Shåuichi, 1949- (World Scientific Pub. Co., 2008)
Coloring in nature comes mostly from inherent colors of materials, though it sometimes has a purely physical origin such as diffraction or interference of light. The latter, called structural color or iridescence, has long been a problem of scientific interest. Recently, structural colors have attracted great interest because various photonic architectures, now developing in modern technologies, have been spontaneously created in the self-organization process and have been extensively used as one of the important visual functions. In this book, the fundamental optical properties underlying structural colors are explained, and these mysteries of nature are surveyed from the viewpoint of biological diversity and according to their sophisticated structures. The book proposes a general principle of structural colors based on the structural hierarchy and presents up-to-date applications.